"I'm 'just' a community pediatrician" views and challenges of pediatricians working in the community in Israel - Shulamit Pinchover; Rony Berger-Raanan; Maya Yaari; Mary Rudolf; Lisa Rubin; Dafna Idan-Prusak; Vera Skvirsky; Tirzah Margolin; Hava Gadassi (BMC, 2023)
Abstract Background There are ongoing changes around the world in the training and practice of pediatricians who work in the community. These changes are driven by the understanding that pediatricians are required to provide not only acute primary care but also to address more comprehensive concerns, particularly the 'new morbidities'. The present study examines the professional identity of Israeli pediatricians in the community in light of these changes, the barriers and challenges to their work and professional adaptations in the field. Methods We used a mixed-methods approach, collecting the perspectives of 137 pediatricians who work in the community through an anonymous online survey, followed by in-depth semi-structured interviews with 11 community pediatricians. Results The survey results show that community pediatricians in Israel have limited knowledge on a variety of developmental, behavioral and emotional issues; that they lack working relationships with medical or other professionals; and are rarely engaged with other community services. Three main themes arose from the interviews that support and deepen the survey results: perceptions of the profession (pediatrics in the community vs. community pediatrics), the stature of pediatricians in the community (during residency, the choice to work in the community, their daily work) and barriers and change in community pediatrics (isolation, limited resources and challenges arising from the nature of community work). Conclusions The present study sheds light on the professional identity and the day-to-day challenges and successes of pediatricians working in the community. Continuing medical education, providing a supportive framework and professional community, better resources, more time with patients, and tools and opportunities for professional development would help pediatricians who work in the community to overcome some of these challenges. The research findings reinforce the need for policy change in the field of community pediatrics with a specific community training curriculum, provision of more resources and ongoing support for pediatricians. This requires partnership between the HMOs, the Ministry of Health, the Scientific Council (Israel Medical Association, professional organizations) and NGOs in order to turn individual-level solutions into system-level and policy-changing solutions.